Encountering the Lovers in the Song of the Songs (2:1): Reading the Allegory Anew and Imagining Sex Education for the 21st Century. - Nugroho, Isodorus Bangkit Susetyo Adi (Universitas Sanata Dharma, 2025)
Traditionally, the lovers in the Song of Songs are often seen as an image of the relationship between God and Israel or humans. Assuming this allegorical interpretation might be accurate, the questions remain. Who are the lovers there? How do we make sense of love's lustful and pleasurable dimension as portrayed in detail throughout the book? Benefiting from the historical and literalist readings, this article shows a new understanding of the lovers in this most erotic narrative in the Judeo-Christian Bible. Then, using the conceptual metaphor approach, the author would analyze one of the metaphors used by the female lover: “I am a rose in the Plain of Sharon, a lily in the valleys (2:1).” Through unpacking this solid self-description metaphor, the author will present the mental map of the female lover, the protagonist character in the book, to help the readers understand the original message of the Songs as pedagogical means for the youth in dealing with human sexuality. Thirdly, through the perspective of the Book of Genesis, the author will help the readers situate the theological sense of God’s love in the Songs properly, as supported by the elements within the text and its socio-historical context. Finally, drawing insight from the Songs, this article will offer practical wisdom in dealing with our human experience of cybersex in the internet era.